The Effectiveness of Technical Guidance on the Teaching Skills of Elementary School Teachers - Pramesti Arumingtyas; Kartika Chrysti Suryandari; Winarno Narmoatmojo (SAINTIS Publishing, 2025)
This study examines the effectiveness of the Independent Curriculum of Technical Guidance (Bimtek) in improving teachers' teaching skills through a structured professional development program. A one-group pre-experimental design, i.e. pre-test-post-test, was used by involving 59 teachers who participated in the training. The findings showed a significant improvement in teaching competence, especially in the application of project-based learning, formative assessment, and interactive teaching strategies. The post-test results showed an average improvement of 14.83 points compared to the pre-test score, which confirms the positive impact of the training. Teachers who received mentoring and post-training coaching showed greater skill improvement than those who only attended self-training sessions. In addition, the In-On-In model has proven to be more effective in encouraging sustainable pedagogical improvement. Despite these positive results, challenges remain, such as time constraints and access to ongoing support, which affect the effectiveness of Technical Guidance in the long term. Compared to other training models, Bimtek offers a cost-effective and adaptable approach to professional development, which ensures practical and sustainable solutions to improve the quality of teaching. These findings highlight the importance of a structured and sustainable teacher training program to support the successful implementation of the Independent Curriculum in primary schools.